Technology-Based Character Education In Islamic Education (Case In MAN 1 Darussalam Ciamis and SMA Islam 5 Al-Azhar Cirebon) - Meliani, Fitri; Munandar, Didih Syakir; Hasanah, Aan; Arifin, Bambang Samsul (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to describe character education through technology-based which is carried out in Islamic schools, namely in the form of extracurriculars at MAN 1 Darussalam Ciamis and digital literacy which is included in the curriculum at Al-Azhar Islamic High School 5 Cirebon.Â This research was conducted in April-May 2022, with the subject of research by the Vice Principal of the Curriculum section and students. The method used is a descriptive method using a qualitative approach. Data collection used several guidelines including interview guidelines, documentation studies, and observations. The results of the research at MAN 1 Darussalam Ciamis showed that: (1) Robotics extracurricular activities are carried out every Thursday at 15.00-end; (2) Activities are carried out at the Robotics Lab, Integrated Religious Laboratory Building; (3) Activities are carried out with the supervision of a teacher and coach; (4) Material taught in robotics extracurricular activities includes material training and work programs. The results of research at Al-Azhar Islamic High School 5 Cirebon show that: (1) Digital literacy activities are included in the school curriculum; (2) Digital literacy activities are carried out in the School Mosque Hall; (3) The activity is attended by all students of class X, XI and XII every Friday at 07.00-08.00 WIB; (4) Digital literacy activities are carried out with the supervision of the Vice Principal of the Curriculum Section and several teachers; (5) The material taught includes training on various digital applications that are useful in learning, and work programs.